Electrode scale and electrolyte transport effects on extreme fast charging of lithium-ion cells. (20th March 2020) - Colclasure, Andrew M.; Tanim, Tanvir R.; Jansen, Andrew N.; Trask, Stephen E.; Dunlop, Alison R.; Polzin, Bryant J.; Bloom, Ira; Robertson, Dave; Flores, LeRoy; Evans, Michael; Dufek, Eric J.; Smith, Kandler
Abstract: A combination of cell testing and electrochemical-thermal modeling is used to investigate extreme fast charging (XFC) performance for cells with a low loading of 1.5 mAh . cm −2 and moderate loading of 2.5 mAh . cm −2 . Cells with a low loading of 1.5 mAh . cm −2 withstand XFC performance remarkably well even up to 9C constant current (CC) charging with high charge capacity, high coulombic efficiency and very little apparent lithium plating. For a moderate loading of 2.5 mAh . cm −2, the 6C CC charge capacity is poor with significant amounts of visually observed lithium plating. Simulated electrolyte transport properties are revealed to be insufficient and majorly set limitations for XFC performance in case of the moderate and the only simulated higher loadings (>2.5 mAh . cm - 2). Charging at elevated temperature is shown to be an effective strategy for moderate loading cells enabling good 10-min charge capacity, high coulombic efficiency, and mitigating lithium plating. Lastly, an electrochemical model is used to investigate strategies for enabling 4–6C CC charging for cells incorporating loading beyond 3 mAh . cm −2 . As a result, the combination of an increased cell temperature, reduced electrode tortuosity, and enhanced ion-transport in the electrolyte are most likely required to facilitate XFC for state of the art and future high energy lithium-ion batteries.